Nurse Managers’ Perception and Practice on the Theory of Technological Competency as Caring in Nursing: A Preliminary Study - Nakano, Yoko; Yokotani, Tomoya; Takashima, Yoshiyuki; Betriana, Feni; Osaka, Kyoko; Kataoka, Mutsuko; Tanioka, Tetsuya; Locsin, Rozzano C (Fakultas Ilmu-ilmu Kesehatan, 2023)
In spite of emphasis on patient-centered care and promotion of their quality, shortcomings have been seen in psychiatric care due to lack of compassion. To improve the quality of psychiatric caring in nursing, it is important to develop and implement in-service education based on Locsin’s Technological Competency as Caring in Nursing (TCCN) theory. Objectives to determine psychiatric nurse managers' perception and practice status as a preliminary survey to serve as a resource for in-service psychiatric nursing education. This survey was conducted in August 2022 using the Technological Competency as Caring in Nursing Instrument-Revised for Practice (TCCNI-Repract) scale at